Daily online contouring and re-planning versus translation-only correction in neurovascular-sparing magnetic resonance-guided radiotherapy for localized prostate cancer. (October 2022) - Teunissen, Frederik R.; van der Voort van Zyp, Jochem R.N.; de Groot-van Breugel, Eline N.; Verkooijen, Helena M.; Wortel, Ruud C.; de Boer, Johannes C.J.
Abstract: Neurovascular bundle (NVB) and internal pudendal artery (IPA) sparing during magnetic resonance-guided radiotherapy (MRgRT) for prostate cancer aims for preservation of erectile function. Our present workflow involves daily online contouring and re-planning on a 1.5 T MR-linac, as alternative to conventional (rigid) translation-only corrections of the prostate. We compared planned dose for the NVB and IPA between strategies. Total planned dose was significantly lower with daily online contouring and re-planning for the NVB, but not for the IPA. For the NVB and IPA, the intrapatient difference between highest and lowest fraction dose was significantly smaller for the contouring and re-planning plans.